079 The impact of the COVID-19 pandemic on the mental health of MND patients. Issue 6 (27th May 2022) - Gilchrist, Abigail; Chaouch, Amina; Ealing, John; Hamdalla, Hisham; Coen, Sharon
Abstract : Background: Motor neurone disease (MND) is an isolating condition that has many implications on patients mental health. Throughout the COVID-19 pandemic, patients with chronic health conditions, including those with MND, have been further removed from the support of their specialist teams. Objectives: 1) To determine the impact of the COVID-19 pandemic on the mental health of the Salford Royal MND patients. 2) To improve the mental health support offered by the service by addressing patient concerns and feedback. Methods: A survey was sent to patients who had been receiving care by the Salford Royal MND Team since the 1st of January, 2020. The answers were reviewed and measures were put in place to address concerns. Patients were resurveyed two months later and answers were compared. Results: Patients reported a higher proportion of issues with their mental health during the pandemic compared to prior. The service was seen as doing adequately but areas were identified to address. Our interventions were largely successful with many patients reporting an increase in the support they receive from the Salford Royal MND Team. Conclusions: Areas of improvement were identified to accommodate the change in the way the Salford Royal MND Team deliver their care. abigail.gilchrist@student.manchester.ac.uk